2013
DOI: 10.5455/2320-6012.ijrms20130506
|View full text |Cite
|
Sign up to set email alerts
|

A prospective survey study on premenstrual syndrome in young and middle aged women with an emphasis on its management

Abstract: Premenstrual syndrome (PMS) is defined as the recurrence of psychological and physical symptoms in the luteal phase, which remit in the follicular phase of the menstrual cycle. Symptoms of which fall in three domains: emotional, physical and behavioural e.g. irritability, anger, headache, fatigue, food cravings etc. The survey study of was conducted among 50 young & 50 middle aged women of S.B.K.S Medical Institute and Research Centre to find the prevalence of premenstrual syndrome with an emphasis on its mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…Reporting of the backache (70.7%) was relatively high in current study, which is in concordance with previous studies [ 17 , 18 ]. However, Antai et al (2004) reported only around 14% incidence of backache [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Reporting of the backache (70.7%) was relatively high in current study, which is in concordance with previous studies [ 17 , 18 ]. However, Antai et al (2004) reported only around 14% incidence of backache [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…More such reports have come from India and Pakistan in general population and in medical setup [ 16 , 17 ]. A recent Indian study also found similar incidence of backache and somatic symptoms in women in healthcare setting [ 18 ]. However, no earlier study has been conducted in psychiatric health care professionals.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The reason for the high prevalence rate of PMDD among participants of the current study may be due to stress related learning or can be justifiable by the fact that the vast majority of participants are single. In this study there was no significant difference between students with PMDD and without regarding physical symptoms which is not in agreement with a study by Brahmbhatt et al (21) who reported that, the overall frequency of somatic complaints was more than that of the abnormal mood and behavior.…”
Section: Discussioncontrasting
confidence: 57%
“… 2 , 3 There is a high incidence of PMS; about 80% of women reported mild premenstrual symptoms, 20%–50% reported moderate symptoms, and about 5% of women had severe symptoms. 4 , 5 Despite the high prevalence of premenstrual syndrome, causes of it have not been clear and several etiologies have been proposed (e.g., hormonal change, neurotransmitters, prostaglandins, diet, drugs, and lifestyle). 6 …”
Section: Introductionmentioning
confidence: 99%